Breastfeeding (rada’ah): an appraisal of the law governing Muslims in Malaysia and several Muslim countries - Mohd, Azizah (Serials Publications, 2022)
Breastfeeding is a common practice, rights and duties involving group of people in many ways. It is known in every human practice as well as many legal systems that emphasize on infants’ health physically, spiritually, psychologically, emotionally, etc., as well as their mothers. Apart from the significance of breastfeeding, Islamic law imposes a duty to breastfeed on parents as one a means to provide maintenance to children in their infancies. This paper examines the concept of breastfeeding governing Muslims in Malaysia, with a comparative overview with several Muslim countries. Our analysis will focus on the adequacy of provisions for breastfeeding governing Muslims in Malaysia, in particular under the State enactments. Our examination of the provisions of the law on breastfeeding in Muslim countries is to provide a sample of laws and best practices relating to breastfeeding in another jurisdiction.